Factors related to preoperative uncertainty among patients with breast cancer in Wenzhou, China: A cross-sectional study - Huaiyu Shen; Khemaradee Masingboon; Niphawan Samartkit (Belitung Nursing Journal, 2023)
Background: One of the most prevalent psychological signs of breast cancer is uncertainty, which is more prevalent in Chinese patients during the preoperative period. Despite the numerous factors contributing to preoperative uncertainty, there is limited relevant research conducted in China. Objective: This study aimed to describe the current state of preoperative uncertainty and to investigate the relationship between anxiety, illness perception, social support, and preoperative uncertainty in patients with breast cancer in Wenzhou, China. Methods: This cross-sectional research used a simple random sampling technique to select 122 participants from a university hospital in Wenzhou, China, from July 2022 to December 2022, employing validated instruments. Descriptive statistics and Pearson’s correlation coefficient were utilized to analyze the data. Results: The average preoperative uncertainty scores of the patients fell within a moderate range (M = 61.92, SD = 7.51). Significant correlations were found between anxiety (r = 0.638, p <0.01), illness perception (r = 0.704, p <0.01), social support (r = -0.481, p <0.01), and preoperative uncertainty. Conclusions: The results can assist healthcare professionals, especially nurses, in recognizing the factors contributing to uncertainty before surgery in patients with breast cancer. This knowledge enables them to promptly address and minimize this issue, leading to improved outcomes.